2005
DOI: 10.3758/bf03193055
|View full text |Cite
|
Sign up to set email alerts
|

Differential relational encoding of categorical information in memory for action events

Abstract: Memory for action phrases is better if the actions are enacted in subject-performed tasks (SPTs) than if they are only listened to in verbal tasks (VTs). This effect is ascribed to better item-specific encoding of SPTs than of VTs. The role of interitem relational information is controversial, and the findings of clustering with categorically structured lists are inconsistent (see Engelkamp, 1998). The present study contributes to clarifying these effects by demonstrating that intentional relational encoding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…A repeated recall may have helped participants to detect the possible organization according to action sequences. In a previous study, for enactment encoding knowledge about list organization (before the study phase) did not affect clustering in recall; however, such pre-information was used in a verbal-learning condition, resulting in better clustering and higher net recall [40]. It could be that observation would benefit in a similar way from explicit information about list structure.…”
Section: Implications Of the Present Findingsmentioning
confidence: 86%
“…A repeated recall may have helped participants to detect the possible organization according to action sequences. In a previous study, for enactment encoding knowledge about list organization (before the study phase) did not affect clustering in recall; however, such pre-information was used in a verbal-learning condition, resulting in better clustering and higher net recall [40]. It could be that observation would benefit in a similar way from explicit information about list structure.…”
Section: Implications Of the Present Findingsmentioning
confidence: 86%
“…Under random presentation of the list items it helped participants in VTs more than in SPTs if they were pre-informed about the categories used in the list (Engelkamp, Seiler, & Zimmer, 2003;. 5 Overall, it seems as if strategic processes may modulate and complete what is going on automatically if categorically structured lists are presented.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the number of gains may differ even if the initial recall and the overall recall do not (Burns & Schoff, 1999;Payne, 1986). In order to demonstrate that also for SPTs the number of item gains and losses can differ if the initial recall level is kept constant, we compared the number of item gains and losses from Experiment 1 of the present study (initial free recall = .37, average free recall = .39) with those from Experiment 3 of another study from our laboratory which happened to produce the same initial (.37) and average free recall level (.40, Experiment 3 of Engelkamp & Seiler, 2002). The only difference of both experiments was that in the present experiment unrelated lists were used and in the other one related lists.…”
Section: Engelkamp and Seilermentioning
confidence: 92%